The Failure of Divorce Mediation: The Role of Attorney in the Mediation Process of Divorce Cases in Indonesia - Robbani, Banaan Iqbal; Putra, Adji Pratama; Suprianto, Agus (UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze the role of an attorney in the mediation process of divorce cases at the Sleman Indonesia Religious Court. In some divorce cases, a lawyer can appear to influence his client (the litigant) in the mediation room. Because of the lawyer's intervention, the disputing parties who initially wanted a settlement change their decision to divorce. This study is a field study whose data is collected through interviews and observations at the Sleman Religious Court. It employed legal ethics theory to analyze the role of an attorney in the divorce mediation process and legal system theory to analyze several factors that cause the failure of divorce mediation, as well as whether an attorney has a role. The results of this study show that many attorneys have carried out their duties by the Advocate Code of Ethics and by the regulations on mediation procedures in the court. However, some advocates still try to influence their clients in the mediation process. From a juridical perspective, it cannot be justified, as it does not follow the law and ethics. However, it is not entirely to blame, because in terms of legal structure, there are mediation facilities at the Sleman Religious Court that are not regulated by the Supreme Court, such as mediation rooms that are not soundproof, so that the attorney hears the conversation between the mediator and the principal.